A combined scoring system for tumor budding and poorly differentiated clusters in colorectal cancer: A retrospective study - Khan, Adil Aziz; Ahuja, Sana; Barman, Sristi; Zaheer, Sufian (Clinical Surgical Oncology, 2025)
Optimal management of stage II colorectal cancer (CRC) patients is complex due to variability in oncologic outcomes. Tumor budding (TB) and poorly differentiated clusters (PDCs) have emerged as significant prognostic factors. This study evaluates the prognostic significance of a combined scoring system of TB and PDCs in CRC patients. A retrospective study included 68 patients who underwent curative surgery. H&E-stained sections were assessed for TB and PDCs. TB was graded according to ITBCC recommendations: Bd1 (0–4 buds), Bd2 (5–9 buds), and Bd3 (≥10 buds). PDCs were counted as clusters of ≥5 ​cells without gland formation: PDC1 (0–4 clusters), PDC2 (5–9 clusters), and PDC3 (≥10 clusters). TB and PDC scores were combined, resulting in a score range of 2–4. Histological sections were also evaluated for lymphovascular invasion (LVI), perineural invasion (PNI), and other pathological parameters. Statistical analyses were performed using Chi-Square and Fisher's exact tests. TB was high in 32.35% of cases and low in 47.06%. High PDCs were present in 47.06% of cases. The combined scoring system showed 55.88% of cases with a score of 3, indicating intermediate risk. Statistical significance was observed between combined scores and T stage, LVI, PNI, histological grade, extranodal extension, and tumor size (p ​< ​0.05). The combined scoring system for TB and PDCs demonstrated superior prognostic performance compared to individual assessments. This system provides a more comprehensive risk stratification, which may guide more tailored treatment decisions in CRC management.